2022
DOI: 10.1101/2022.09.27.509758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vesicles driven by dynein and kinesin exhibit directional reversals without external regulators

Abstract: Intracellular transport along cytoskeletal filaments propelled by molecular motors ensures the targeted delivery of cargoes to their destinations. Such transport is rarely unidirectional but rather bidirectional, including intermittent pauses and directional reversals owing to the simultaneous presence of opposite-polarity motors. It has been unclear whether such a complex motility pattern results from the sole mechanical interplay between opposite-polarity motors or requires external regulators. Here, we addr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Specifically, we model the kinesin tail as a Hookean spring with a set rest length that only allows the kinesin motor to bind the MT when the liposome is optimally positioned at a specific distance from the MT. This is in contrast to other models (20, 21, 32) which allow binding of the kinesin to the MT at any distance less than or equal to the length of the kinesin tail, i.e., a highly flexible or compressible tail. In our model, once the first motor binds, it restricts the spatial freedom of the liposome, making it more difficult for additional motors to bind the MT, providing a potential reason for anti-cooperative kinesin binding, similar to prior observations with myosin-Va (22, 23).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Specifically, we model the kinesin tail as a Hookean spring with a set rest length that only allows the kinesin motor to bind the MT when the liposome is optimally positioned at a specific distance from the MT. This is in contrast to other models (20, 21, 32) which allow binding of the kinesin to the MT at any distance less than or equal to the length of the kinesin tail, i.e., a highly flexible or compressible tail. In our model, once the first motor binds, it restricts the spatial freedom of the liposome, making it more difficult for additional motors to bind the MT, providing a potential reason for anti-cooperative kinesin binding, similar to prior observations with myosin-Va (22, 23).…”
Section: Discussionmentioning
confidence: 66%
“…S5 and S7) which, in our model, results from small individual teams of kinesin-1s on the liposome surface being simultaneously engaged with both of the intersecting MTs and thus undergoing a tug-of-war, as suggested previously (12, 13, 15, 22). Since the number of engaged motors in either team is stochastic and generally varies between 1-3 motors, it’s this dynamic motor binding and unbinding within a team (32) (Figs. 3B and 3C) that contributes to the eventual directional outcome, which is simply dictated by the motor team that wins the tug-of-war (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon typically coincided with an abrupt change in the direction of cell movement or comparatively low gliding velocities (<1.5 µm•s -1 ), suggesting that these myosins can generate opposing forces in each half of the cell. Opposing forces play an important role in many cytoskeletal processes including bidirectional transport of vesicles, cell size determination, and actin ring formation in cytokinesis, which rely on similar tug-of-war systems between motors [51][52][53] . In vitro experiments have also shown that groups of molecular motors pulling in opposite directions can cause spontaneous symmetry breaking 54 and distinct modes of slow and fast movements, as well as sharp transitions between these modes 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that active dynein and kinesin motors engage in a tug-of-war when artificially coupled 66,67,68,69,70,71 . However, the relevance of such mechanical antagonism in localizing physiological cargoes for these motors is unresolved 6 .…”
Section: Co-ordination Of Kinesin-1 and Dynein Motors On Osk Rnpsmentioning
confidence: 99%